Out of India selected stories - Jhabvala, Ruth Prawer 1927-2013 (Morrow, 1986)
Contains fifteen short stories selected from four previous collections and all set in India.
Keywords: Alltag, Brauchtum; Indien; India -- Social life and customs -- Fiction